An investigation of learning analytics in an online video-based learning platform - Sim, Ethan H. C.; Lau, Sian Lun * (2020)
Using an online platform as a teaching and learning tool has been more common since the last decade. An advantage of this approach is the ability to capture implicit information, and hence learning analytics may be implemented to assist improvement in learning experience and efficiency. Thus, this paper aims to investigate and identify what features are needed by stakeholders to be included in an online video-based learning platform in order to implement learning analytics. A prototype learning platform has been developed. It has been evaluated through a survey by a group of testers to obtain feedback and review regarding their learning and usage experience. The majority of the participants of the survey have shown interest in the features implemented by the system and would like to see these features implemented in a working video learning platform.